Challenges in the management of a rare case of caudal duplication syndrome in a poor resource setting - E. Bandré; A. Wandaogo; S.M. Kabre; I. Ouedraogo; M. Napon (Elsevier, 2015)
Caudal duplication syndrome is a series of malformations affecting the development of the caudal area of the embryo involving a combination of malformations of the digestive tract, the genitourinary tract, the spinal column, the limbs or the neural tube. The authors report a case characterized by a supernumerary lower limb comprised of a thigh, leg, two feet joined by their medial edge and two scrota each containing one testicle and two phalluses, one of which lacks a urethral. The second phallus had an apical urethral meatus allowing for normal urination, a hemi-thoracic vertebrae, a megaureter and a single kidney and supernumerary vertebrae. A surgical excision of the supernumerary limb and the abormal phallus was performed, followed by a fusion of the two scrota. The surgical outcomes were uneventful.